2019
DOI: 10.1055/a-0973-0067
|View full text |Cite
|
Sign up to set email alerts
|

Anti-plasmodial Effects of Zanthoxylum zanthoxyloides

Abstract: Zanthoxylum zanthoxyloides, syn. Fagara zanthoxyloides, is a tree growing in West Africa and is used in traditional medicine against a variety of diseases, including malaria. In the work reported here, root bark and stem bark extracts of this tree, as well as compounds isolated from the extracts, have been investigated for activity in vitro against chloroquine-sensitive and chloroquine-resistant strains of Plasmodium falciparum. In addition, toxicity against nauplii of the brine shrimp Artemia salina has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Based on the use of different Z. zanthoxyloides parts for treating malaria ( Adesina 2005 ; Enechi et al, 2019 ), Goodman et al (2019) that four alkaloids, bis-dihydrochelerythrinyl ether, skimmianine, buesgenine and chelerythrine, isolated from roots, root-bark and stem-bark exhibited anti-plasmodial activity against chloroquine-sensitive (3D7) strains of P. falciparum (IC 50 values of 4.3, 0.7, 2.0, and 0.4 μg/ ml, respectively). Previous studies on other alkaloids showed that nitidine from Z. gilletii stem bark exhibited anti-plasmodial activity against P. falciparum strain FcB1 with IC 50 < 5 μg/ml by halting DNA synthesis in the parasite ( Zirihi et al, 2005 ; Zirihi et al, 2009 ).…”
Section: Zanthoxylum Species As Potential Source Of Anti-parasitic Agentsmentioning
confidence: 99%
“…Based on the use of different Z. zanthoxyloides parts for treating malaria ( Adesina 2005 ; Enechi et al, 2019 ), Goodman et al (2019) that four alkaloids, bis-dihydrochelerythrinyl ether, skimmianine, buesgenine and chelerythrine, isolated from roots, root-bark and stem-bark exhibited anti-plasmodial activity against chloroquine-sensitive (3D7) strains of P. falciparum (IC 50 values of 4.3, 0.7, 2.0, and 0.4 μg/ ml, respectively). Previous studies on other alkaloids showed that nitidine from Z. gilletii stem bark exhibited anti-plasmodial activity against P. falciparum strain FcB1 with IC 50 < 5 μg/ml by halting DNA synthesis in the parasite ( Zirihi et al, 2005 ; Zirihi et al, 2009 ).…”
Section: Zanthoxylum Species As Potential Source Of Anti-parasitic Agentsmentioning
confidence: 99%
“…Moreover, it is possible that the highlighted activity comes from the presence of minor compounds, as well as from the synergy between different molecules. Nevertheless, studies were carried out on Z. leprieurii and other species of Z. chalybeum and Z. zanthoxyloides plant extracts, showing high anti-plasmodial activities [79][80][81][82], all of which supports the effective use of Zanthoxylum species in traditional medicine for the treatment of malaria.…”
Section: Anti-plasmodial Activitymentioning
confidence: 99%
“…The vast majority of people who use plant extracts as medicine consider them safer compared to synthetic drugs [ 1 ]. In addition, many types of infections, parasitic diseases, and tumors that are resistant to some synthetic drugs have been shown to be treatable using herbal medicines [ 1 , 2 , 3 , 4 , 5 ]. Furthermore, phyto-bioactive compounds have been shown to provide templates that direct the development of some drugs in current use, such as quinine and artemisinins for malaria, and alkaloids and camptothecins for cancer.…”
Section: Introductionmentioning
confidence: 99%